Nano-Coating of Chitosan Incorporated with Cinnamomum Zeylanicum Es sential Oil: Application on Chicken Sausages for Quality Enhancement and Shelf-Life Extension - Shreya Rao, Neelagiri; Shukla, V H; Zende, R J; Vaidya, V M; Ingole, S D (Journal of Meat Science, 2026)
The application of edible coatings containing nanoemulsions of essential oil is  a growing area of research for quality enhancement of meat and meat products  using natural preservation methods. The present work was done to evaluate  the quality and shelf-life of chicken sausages coated with an edible coating of  nanoemulsions of chitosan and cinnamon essential oil. A total of four types of  edible coatings were prepared, viz. T1: 0.3 % chitosan only; T2: 0.3% chitosan  and 0.3% cinnamon essential oil; T3: nanoemulsion of 0.3% chitosan; T4:  nanoemulsion of 0.3% chitosan incorporated with 0.3% cinnamon essential  oil. The edible coatings were characterized and chicken sausages were coated  with the developed edible coatings while determining the quality and shelf-life  at regular intervals during refrigeration storage.: UV-Vis spectrophotometry,  particle size analysis, and HR-TEM analysis revealed the spherical-shaped  nanoparticles in the 50-200 nm range. Edible coatings significantly (P
Keywords: Chitosan; Cinnamon essential oil; Nanoemulsion; Edible coating; Natural preservation; Shelf-life extension